ANALYSIS OF QUALITY WORK OF LIFE, WORK DISCIPLINE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON THE PERFORMANCE OF ASN IN THE OFFICE REGIONAL SECRETARIAT OF GOVERNMENT OF BINJAI - M Fariz Al Hafiz; Prihatin Lumbanraja; Iskandarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research was conducted at the Regional Secretariat Office of Pemko Binjai located at L. Jend. Sudirman, No. 6, Binjai, Kec. Binjai, Binjai City, North Sumatra. The time of this research was conducted from March to May 2023. Based on the results of processing research data obtained from employees of the Regional Government Secretariat of the City of Binjai, the following conclusions can be conveyed as follows, Quality of Work Lifeeffect on Employee Performance at Regional Secretariat of Government of Binjai City. Work Discipline influences Employee Performance Regional Secretariat of Government of Binjai City. Organizational Citizenship Behavioreffect on Employee Performance atRegional Secretariat of Government of Binjai City. Quality of Work Life,Work Discipline andOrganizational Citizenship Behaviorsimultaneously affect the performance of employees atRegional Secretariat of Government of Binjai City.